2013
DOI: 10.1371/journal.pone.0079481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Frizzled Homolog 3 Protein in Colorectal Cancer Patients

Abstract: Frizzled homolog 3 receptor was up-regulated in several gastrointestinal cancers such as esophageal and gastric cancers. Moreover, frizzled homolog 3 has recently reported to be expressed in colorectal adenoma specimens. In the present study, we investigated the clinical significance of frizzled homolog 3 protein in colorectal cancer patients. Using immunocytochemical staining, frizzled homolog 3 expression was examined in 186 colorectal cancer specimens, 79 colorectal adenoma specimens, 133 colorectal polyp s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…27 An immunocytochemical study showed that FZD3 is strongly associated with CRC progression. 28 Additional studies on miR-4500 and its target genes may be helpful for understanding tumorigenesis. Collectively, similar to the let-7 family, the potential tumor suppressor miR-4500 may affect tumorigenesis by targeting many critical oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…27 An immunocytochemical study showed that FZD3 is strongly associated with CRC progression. 28 Additional studies on miR-4500 and its target genes may be helpful for understanding tumorigenesis. Collectively, similar to the let-7 family, the potential tumor suppressor miR-4500 may affect tumorigenesis by targeting many critical oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…As a transmembrane receptor and activator of the Wnt/beta-catenin pathway, FZD3 interacts with Wnt and activates Dishevelled (DSH) to recruit other components of the destruction complex, thereby, reducing beta-catenin degradation. The blocked degradation of beta-catenin leads to an accumulation of beta-catenin in the nucleus and upregulation of oncogenic activity (22, 31). FZD3 is known to be overexpressed in CRC tissues and cell lines, and is highly correlated with CRC progression (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…The blocked degradation of beta-catenin leads to an accumulation of beta-catenin in the nucleus and upregulation of oncogenic activity (22, 31). FZD3 is known to be overexpressed in CRC tissues and cell lines, and is highly correlated with CRC progression (31, 32). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated the involvement of several Frizzled receptors, including FZD8, FZD2, FZD3, FZD4, FZD5, FZD6, FZD7, and FZD10 in different cancers. Though Frizzled receptors function as key components of the Wnt signaling pathway, the specific link with the ETS‐related transcription factor ERG is unknown.…”
Section: Discussionmentioning
confidence: 99%